1999
DOI: 10.1063/1.873457
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature dynamic hohlraums on the pulsed power driver Z

Abstract: In the concept of the dynamic hohlraum an imploding Z pinch is optically thick to its own radiation. Radiation may be trapped inside the pinch to give a radiation temperature inside the pinch greater than that outside the pinch. The radiation is typically produced by colliding an outer Z-pinch liner onto an inner liner. The collision generates a strongly radiating shock, and the radiation is trapped by the outer liner. As the implosion continues after the collision, the radiation temperature may continue to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…The imprint of such an azimuthal structure has been observed from the radiation field generated from foam targets placed interior to the wire array by , Derzon et al [32]. Nash et al [33] have shown by replacing the posts with an azimuthally continuous shell that the on-axis radiation generated from a dynamic hohiraum configuration is doubled, again illustrating the importance ojmaintairzing azh.m.h-d symmetry throughout the entire ioad region for producing high radia!ion yields.…”
Section: Tip Simulationsmentioning
confidence: 76%
“…The imprint of such an azimuthal structure has been observed from the radiation field generated from foam targets placed interior to the wire array by , Derzon et al [32]. Nash et al [33] have shown by replacing the posts with an azimuthally continuous shell that the on-axis radiation generated from a dynamic hohiraum configuration is doubled, again illustrating the importance ojmaintairzing azh.m.h-d symmetry throughout the entire ioad region for producing high radia!ion yields.…”
Section: Tip Simulationsmentioning
confidence: 76%
“…These diagnostics included a total-energy bolometer, a faltered XRD set, and faltered fast-framing pin-hole cameras. Additionally, on some shots the hohlraum was removed and the power exiting the REH was measured by a further suite of on-axis diagnostics [22,25,48]. For these measurements, Lambertian emission at the REH was assumed.…”
Section: Experimental Arrangementfmentioning
confidence: 99%
“…At Sandia National Laboratories, for example, three hohlraum concepts that take advantage of the high x-ray powers generated with thk new pulsed-power capability are under development to investigate the feasibility of z-pinches to drive ICF targets [18][19][20][21][22]. They are referred to as the z-pinch driven [23,24], the dynamic [25,26], and the static-wall hohlraum [27]. To date, the large-volume z-pinch driven hohlraum has developed a temperature of 95*5 eV in a 17-mm diameter by 15-mm high hohlraum, when heated by radiation generated external to a single pinch [28], The energy-efficient dynamic hohlraum, which uses radiation generated internal to a radially converging target heated by the imploding wire array, has developed temperatures ranging from 80 to 180 eV as the diameter of a 10-mm high hohlraum compresses from 5 to 1.6 mm [22].…”
Section: Introductionmentioning
confidence: 99%
“…Implicit in these applications is the assumption that the axial radiation produced is top-bottom symmetric [18]. Sandia's initial DH configuration was developed by Nash and colleagues [3], after it was established that a high x-ray power could be generated by a wire-array z-pinch if a large number of wires were used in the array [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic-hohlraums (DHs) [1][2][3][4] driven by a wire-array z-pinch are being developed and used as intense blackbody x-ray sources for inertialconfinement-fusion (ICF) [5][6][7][8][9] and hightemperature radiation-flow experiments [10][11] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%